Analysis of Brand Image and Excellent Service of Indomaret Minimarket on Purchasing Decisions with Innovation as Mediation During The Pandemic - Setiarini Setiarini (PT Mattawang Mediatama Solution, 2023)
This research aims to analyze the influence of Brand Image and Excellent Service in Indomaret minimarkets on Purchasing Decisions with Innovation as a mediator during the pandemic. This research uses the Structural Equation Modeling method. SEM allows the analysis of a series of relationships simultaneously, provides flexibility in assumptions, and allows the testing of models with many dependent variables. The sampling method used was convenience sampling, involving 252 respondents. The results of the analysis show that Brand Image has a positive and significant influence on Innovation and Purchasing Decisions at Indomaret. Excellent Service also has a positive and significant influence on Innovation but does not have a direct significant influence on Purchasing Decisions. Innovation has a positive and significant influence on Purchasing Decisions. This research concludes that Brand Image has an important role in influencing Innovation and Purchasing Decisions at Indomaret. Excellent Service influences Innovation but does not directly influence Purchasing Decisions. Innovation has a significant role in influencing Purchasing Decisions. Therefore, companies need to maintain and strengthen a positive brand image, continue to improve service quality, and innovate to remain competitive in the market, especially in a pandemic situation.